PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT. MANDIRI TUNAS FINANCE PEKANBARU - Suci Mayang Sari; Jushermi Jushermi; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Marketing is an important activity in a company, because the activity is intended to add and stream the flow of goods and services from producers to consumers. Marketing activity itself is an activity done by the company, from start pricing planning, distributing and promoting products produced by the company, in order to meet the needs. This study aims to see the influence of price and promotion of purchasing decisions at PT. Mandiri Tunas Finance Pekanbaru. The research used in this research is price and promotion as independent variable and purchase decision as dependent variable. Population in this research is customer of PT. Mandiri Tunas Finance Pekanbaru amounted to 147 people in 2017. Techniques taken in the sampling that is, probability sampling and non probability sampling. And to determine the number of samples in this study using Slovin formula with 10% error limit, and obtained the number of samples as much as 60. Data analysis method used is descriptive analysis and multiple linear regression analysis using SPSS 21 program. The results of the study found that the price significantly influence the purchase decision at PT.Mandiri Tunas Pekanbaru. Then the promotion has a significant effect on purchasing decisions at PT. Mandiri Tunas Finance Pekanbaru. The percentage of price influence and promotion on purchasing decision is 71,4%. It is expected that the company can continue to strive to price competitiveness that can improve purchasing decisions on the customer to use the services at his company.Keywords: Price, Promotion and Purchase Decision.